Formations and properties PHOTOCATALYTICally active thick films with dioxide titanium - K. V. Ashurkevich; I. A. Nikolaenko; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Photocatalytically active porous films as thick as 20 µm were fabricated from the paste composed of sodium silicate solute and nanodispersed TiO2 powder fired at 200 to 400°С on glass substrates. It was shown, that the porosity of films can be extended by chemical etching, that allows an increase of the effective surface up to 30 m2/g. The photocatalytic activity of the films was estimated by decomposition the organic dye which was aqueous solution of methylene blue subjected to ultraviolet radiation.